OPTIMASI DESAIN AKUSTIK BANGUNAN KONSERVASI PADA RUANG SERBAGUNA SALLE FRANCE CCCL SURABAYA - C. Indrani, Hedy; Tansajaya, Felicia (Institute of Research and Community Outreach - Petra Christian University, 2011)
In multi-function rooms, the acoustic system usually becomes a vital issue because speech and music truly depend on sound in delivering message. The accuracy of a message and its meaning delivered to the audience increases with the quality of the acoustic system of the room. Conversely, choosing and applying the right materials for the interior elements and furnitures is truly vital in creating a good acoustic system. Results of observation in the multi-function room of Salle France CCCL Surabaya reveal the poor reverberation time and sound insulation of the room. This study uses the quantitative research method in which field data are analyzed and verified to determine the reverberation time, acoustic response and sound insulation. This process was done by using manual calculation as well as computerized calculation using the Autodesk Ecotect Analysis 2010 software. The process of optimizing the acoustic design system was then performed while still considering the rules of conservation buildings to achieve the optimum design solution. The results of optimization revealed that addition of new elements in the interior of the Salle France multi-function room is required that are not permanent and could be returned to their original form so that they abide by the main rules of conservation buildings. Attempts to insulate sound were done by adding new elements such as glasswool, rubber, eva sponge, sealant and acourette mat in ceilings, cable holes, keyholes, slots, and jalousies on the door to prevent sound leaks from the room.